Pengaruh Keterampilan Metakognitif terhadap Hasil Belajar Mahasiswa Pendidikan Akuntansi pada Mata Kuliah Pengantar Akuntansi 1 di Universitas Negeri Makassar - Adelia Sartika; Sitti Hajerah Hasyim; M. Ridwan Tikollah (Departement of Mathematics Education, 2024)
This research aims to understand the influence of Metalcognitive Skills on Halsil Belaljalr Malhalal School of Mathematics Education students in Malthal College of Mathematics 1 at Malkalssalr State Universities. The variables in this research are metacognitive skills as the independent variable (X) and learning outcomes of accounting education students as the dependent variable (Y). The population of this research is students from the accounting education study program class of 2019, class of 2020, and class of 2021, totaling 258 students. The sampling technique uses simple random sampling. Data collection was carried out using questionnaires and documentation. The data analysis techniques used are descriptive analysis, instrument testing consisting of validity and reliability tests, and hypothesis testing consisting of simple linear regression analysis, Pearson product moment correlation analysis, coefficient of determination and t-test. The results of this research show that the results of descriptive analysis show that metacognitive skills obtained an average actual score of 80.7 percent, which is in the very high category, while student learning outcomes obtained an average score of 91.07, which is in the very high category. The results of data analysis obtained a simple linear regression equation model Y = 50.657 + 0.333 From the analysis of the efficiency of determination (r2) it was obtained that it was 0.386 or 38.6 percent. This means that metacognitive skills contribute to the learning outcomes of accounting education students by 38.6 percent and the remaining 61.4 percent is influenced by other factors. And from the results of the t-test, a significance value of 0.000 <0.05 was obtained, which means that there is a significant influence between metacognitive skills on the learning outcomes of accounting education students, therefore the hypothesis is accepted.